Application of propyl gallate alleviates pericarp browning in harvested longan fruit by modulating metabolisms of respiration and energy. (1st February 2018) - Lin, Yifen; Lin, Yixiong; Lin, Hetong; Chen, Yihui; Wang, Hui; Shi, John
Highlights: Propyl gallate (PG) decreased activities of CCO and AAO in longan pericarp. PG increased NADK activity and NADP(H) content in longan pericarp. PG increased ATP level and mitochondrial ATPase activity in longan pericarp. PG-delayed longan pericarp browning via altering respiratory pathway. PG-delayed longan pericarp browning related to sufficient ATP and energy charge. Abstract: Effects of propyl gallate on metabolisms of respiration and energy of harvested 'Fuyan' longans and its relationship to pericarp browning were investigated. Compared to control longans, propyl gallate could reduce ascorbic acid oxidase (AAO) activity, lower cytochrome C oxidase (CCO) activity during early-storage and mid-storage, increase NADK activity, elevate contents of NADP and NADPH, decrease contents of NAD and NADH, in addition, lower the decreases of ATP content and energy charge (E.C.), increase activities of mitochondrial H + -ATPase, Ca 2+ -ATPase and Mg 2+ -ATPase during early-storage and mid-storage. Above results suggested that propyl gallate-retarded browning development in pericarp of harvested longans was resulted from decreases in activities of respiratory terminal oxidases like CCO and AAO, increase in proportion of pentose phosphate pathway (PPP) to Embden-Meyerhof pathway (EMP) and tricarboxylic acid (TCA) cycle, and maintenance of mitochondrial integrity via retaining higher levels of ATP content and energy charge, as well as higher activities of mitochondrial ATPase.